Trouvaille information application - Nur Asyiqin, Shakri (2018)
Malaysia is one of Southeast Asia's best travel destinations, possessing an endless range of attractions and activities that cater for the nature-lover, historical buff, cosmopolitan shopper and cultural enthusiast. Based on discussion with the client, their a few problem statements have been given. The problems starter when the tourist wants to tourism other place that are still using the manual process such as the using map and ask people around about new place. For that reason, this study embarks on three objectives which are, to identify the requirement for Trouvaille Information Application, to develop Trouvaille Information Application, and to evaluate the functionality of the proposed application. Hence, Rapid Application Development (RAD) method had been used to shorten the process of developing the Trouvaille Information Application. The expected result of this Trouvaille Information Application is can be one of the travel mobile application that can be use by tourist. Moreover, the significances of this project are the application will display the place information to the user based on their location and searching, provide the suggestion as planning tourism to user and the application will display another user location. The scope of this project is to build and develop a mobile application that related to Trouvaille Information Application. Therefore, it can be describing as the application will be developed for client to provide an application that can help the tourist to tour the new place.